Sustainability evaluation of Indian Eco-Village Development -Project - Laitinen, Jaana (2010)
The main aim of this study is to examine the sustainability level of an environmental development project called Eco-Village Development that is implemented in India, state of Rajasthan. The project started in 2002 and will end in 2010. It is cooperation between the Student Union of the University of Jyväskylä (JYY) and two Indian non-governmental organizations, Women’s Action for Development (WAFD) and Integrated Sustainable Energy and Ecological Development Association (INSEDA). The project is mainly financed by the Ministry for Foreign Affairs of Finland. Goal of this study is to provide recommendations on how to enhance the sustainability of the project’s positive outcomes. The study concentrates on participation and gender and their role in maintaining the project’s benefits. In this research, participation is presented with Amartya Sen’s and Jean Drèze’s perceptions, clarifying its role as a freedom and pointing out how social change can only happen through widespread participation. It can be claimed that high level stakeholder participation is an imperative for projects’ sustainability. The study has been conducted in a form of empowerment evaluation and supported with more traditional participatory methods. Empowerment evaluation provides a philosophy, theoretical framework, and methods to address the concerns of self-assessment and it employs both qualitative and quantitative methodologies. Generally evaluations are seen as learning tools to improve the implementation and particularly the democratic evaluations, such as empowerment evaluation, enhancing the democracy and contributing to good governance. The empowerment evaluation disclosed that the participation among the project volunteers is rather active and both genders seem to have relatively good possibilities to join, plan and implement the actions. Nevertheless, to enhance the participation level and thus the commitment towards the project, which again should lead to higher level of sustainability, it is recommended that as much awareness raising opportunities will be offered to the volunteers as possible. This is due to the fact that learning is greatly valued among the project participants. In order to ensure even higher level of sustainability of the positive outcomes, these trainings should be open for other villagers as well, not only for the volunteers. In addition, women’s participation through village level women groups should be systematically given more attention. This is a substantial component that can engage a majority of the women and thus spread the knowledge into most of the families. Additionally the empowerment evaluation revealed that more attention should be given for forming well functioning youth groups and a Farmer’s Cooperative. However, even though awareness has been well and widely spread, there is still an obstacle on implementing some of the project’s components; money. For this challenge an answer could be micro-financing. As a last note it is proposed that the collaborating NGOs continue staying in touch and keep supporting each other, even though the funding ceases.